Explaining the UCR-NCVS Convergence: a Time Series Analysis - Ansari, Sami (Asian journal of criminology, 2017)
The study intends to explain the convergence of the UCR and NCVS data series (1973-2008). Hypothesized explanatory variables include increased police productivity, change in people’s attitudes toward crime and the police, demographic changes, changes in the measurements used in data collections, and the advancement of telecommunication tools. The time series models with relevant predictor variables are estimated to explain the convergence of the two crime data series in five different crime categories. The results show that an increase in the total number of employees in the police, changes in measurements, especially the methodological changes adopted in the victimization survey in 1992, and changing attitudes toward crime and the police affect the relationship between the two crime data series and may have helped the convergence of the two. We argue that (1) the convergence of the two crime data series is not a mere convergence of methodological inadequacies resulting from the declining quality of the victimization survey and (2) all the predictor variables only partially affect the convergence of the two crime data series. Methodological limitations of this study are also addressed.